Combined Anti‐CD154/CTLA4Ig Costimulation Blockade‐Based Therapy Induces Donor‐Specific Tolerance to Vascularized Osteomyocutaneous Allografts. Issue 7 (23rd February 2016) - Lin, C. H.; Wang, Y. L.; Anggelia, M. R.; Chuang, W. Y.; Cheng, H. Y.; Mao, Q.; Zelken, J. A.; Lin, C. H.; Zheng, X. X.; Lee, W. P. A.; Brandacher, G.
Abstract : Tolerance induction by means of costimulation blockade has been successfully applied in solid organ transplantation; however, its efficacy in vascularized composite allotransplantation, containing a vascularized bone marrow component and thus a constant source of donor‐derived stem cells, remains poorly explored. In this study, osteomyocutaneous allografts (alloOMCs) from Balb/c (H2 d ) mice were transplanted into C57BL/6 (H2 b ) recipients. Immunosuppression consisted of 1 mg anti‐CD154 on day 0, 0.5 mg CTLA4Ig on day 2 and rapamycin (RPM; 3 mg/kg per day from days 0–7, then every other day for 3 weeks). Long‐term allograft survival, donor‐specific tolerance and donor–recipient cell trafficking were evaluated. Treatment with costimulation blockade plus RPM resulted in long‐term graft survival (>120 days) of alloOMC in 12 of 15 recipients compared with untreated controls (median survival time [MST] ≈10.2 ± 0.8 days), RPM alone (MST ≈33 ± 5.5 days) and costimulation blockade alone (MST ≈45.8 ± 7.1 days). Donor‐specific hyporesponsiveness in recipients with viable grafts was demonstrated in vitro . Evidence of donor‐specific tolerance was further assessed in vivo by secondary donor‐specific skin graft survival and third‐party graft rejection. A significant increase of Foxp3 + regulatory T cells was evident in tolerant animals. Donor cells populated peripheral blood, thymus, and both donor and recipient bone marrow. Consequently, combined anti‐CD154/CTLA4Ig costimulation blockade‐based therapy induces donor‐specific tolerance in a stringent murine alloOMC transplant model. Abstract : A short course of combined anti‐CD154/CTLA4Ig costimulation blockade and rapamycin‐based therapy induces donor antigen–specific tolerance in a fully MHC‐mismatched murine vascularized composite allotransplantation model as long as it includes an intragraft vascularized bone marrow component.